Model making as a cognitive tool for the beginners - Sharif, Roslina; Maarof, Shafizal; Abd Rahim,; Nur Afiqah,; Ahmad Amirul,; Ayu Amira,; Mohd Firdaus, (Serdang, Selangor, 2014)
Moulding and training the design thinking and thought process of the early design students are some of the challenges faced by the instructors in the first year of architectural design program in many architectural schools. One of the first important skills that they need to acquire is the ability to perceive or conjure up 3-dimensional images, from the derivatives of the manipulation of a 2-dimensional objects or drawings. In other words, the fledging designer visual thinking is trained to arrive at a 3-dimensional image from their 2 dimensional designs or sketches. The best way to do this is through the use of conceptual model, study models or preliminary models and finally arriving at the final model/design. The writing presents the analysis and evaluation of model-making application in the new architectural student design thinking and the use of models as cognitive tools.